Graphene-like quaternary compound SiBCN: A new wide direct band gap semiconductor predicted by a first-principles study. (31st May 2017) - Qian, Yan; Wu, Haiping; Kan, Erjun; Deng, Kaiming
Abstract: Due to the lack of two-dimensional silicon-based semiconductors and the fact that most of the components and devices are generated on single-crystal silicon or silicon-based substrates in modern industry, designing two-dimensional silicon-based semiconductors is highly desired. With the combination of a swarm structure search method and density functional theory in this work, a quaternary compound SiBCN with graphene-like structure is found and displays a wide direct band gap. The band gap is of which is just between ∼2.20 and of the highlighted semiconductors SiC and GaN. Notably, the following calculation reveals that SiBCN possesses high carrier mobility with and for electron and hole, respectively. Furthermore, the ab initio molecular dynamics simulations also show that the graphene-like structure of SiBCN can be well kept even at an extremely high temperature of 2000 K. The present work tells that designing multicomponent silicides may be a practicable way to search for new silicon-based low-dimensional semiconductors which can match well with the previous Si-based substrates.